Heuristics-based indoor positioning systems: a systematic literature review. (2nd July 2016) - Lam, Luan D. M.; Tang, Antony; Grundy, John
Abstract : Context : Many heuristics-based indoor positioning approaches have been developed to enhance positioning estimation. However, there is no comprehensive survey of these heuristics information and methods. Objective : The main objective of this study is to provide a holistic view and an in-depth analysis of what heuristics information and methods have been used, their general achievements and limitations. This study aims to provide a comprehensive summary to facilitate further research on indoor positioning heuristics. Method : We conducted a systematic literature review (SLR) on indoor positioning heuristics. Results : Ninety-three (93) primary studies were selected. We found two general types of heuristics information and four primary heuristics methods, which we summarised in this paper. We also found that many of these positioning heuristics are tested in experimental settings only. Some heuristics claim practical applications but are not tested for the challenging and typical indoor environments. Conclusion : Most existing heuristics information and methods rely on the assumptions that may not be true in real life environment, hence limiting the usefulness of the positioning outcomes. Based on the analysis of this SLR, we propose two research directions to enhance positioning estimation.